PENINGKATAN LITERASI DIGITAL SISWA MA MODEL ZAINUL HASAN GENGGONG, PROBOLINGGO - Nurhasana, Sri; Yusman, Beny (Gandhi: Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of digital technology brings both challenges and opportunities for students, especially adolescents in Islamic boarding school-based educational environments. A low understanding of digital literacy, data security, and social media ethics can negatively impact the learning process and character development of students. This Community Service (PKM) activity aims to improve the digital literacy of students at MA Model Zainul Hasan Genggong through a socialization program and training in the intelligent, safe, and wise use of digital technology. The methods used include socialization, practice-based training, and evaluation through pre- and post-tests. The activity participated in 30 students. The results of the activity showed a significant increase in students' digital literacy understanding, with an average pre-test score of 46.3 increasing to 82.1 in the post-test. These findings indicate that the digital literacy program is effective in increasing knowledge, awareness of digital security, and ethics in the use of digital media. This activity is expected to become a model for strengthening digital literacy in Islamic boarding school environments